Finance and Development, June 1982. (Finance and Development; Finance and Development ;, 1982)
This paper reviews the World Bank's graduation policy. Graduation of borrowers from the World Bank is a firmly established principle and has been a long-standing practice. Graduation is a logical step in the development process, and a clear set of guidelines for graduation from Bank lending is required. Graduation should be a flexible and fair process, sensitive to each country's individual circumstances. The paper highlights that the graduation policy was reaffirmed at a meeting of the Bank's Board of Executive Directors.